Lead Oxide-Graphite Composite Electrode for pH Measurement - Nepal, Ranjan; Pradhananga, Raja Ram (Nepal Journal of Science and Technology, 2015)
Lead oxide-graphite composite electrode for pH measurement had been fabricated with different percentage of PbO2 in the composite. The proportions of lead oxide affected the sensitivity of the electrode. The electrode composed of 50% lead oxide and 50% graphite gave reproducible result and behaved in Nernstian manner with a potential gradient of -58.8±0.3 mV per unit change in pH. Metal ions such as iron (II), iron (III) and lead (II) interfered in the measurement of pH, while silver (I), copper (II), oxidizing agents such as dichromate and permanganate do not interfere. In absence of interfering ion, the lead oxide-graphite composite electrode could be used for the measurement of pH from 2 to 11. This electrode can also be used as an indicator electrode for acid base titrations. Low cost, quick response, easy to fabricate are some of the advantages of the lead oxide-graphite composite electrode. This electrode is also found to be sensitive to Pb2+ -ions and can be used as a Pb2+-ion sensor up to 10-4M. DOI: http://dx.doi.org/10.3126/njst.v15i1.12015 Nepal Journal of Science and Technology Vol. 15, No.1 (2014) 61-66